Transformasi Dakwah Diera Digital: Analisis Penyampaian Hadis Dalam Konten Media Sosial - Nurhayati, Nurhayati; Ramadhani Siregar, Suci; Susana, Nita; Niswa, Saidatin; Manik, Zulfirman (JURNAL SYIAR-SYIAR, 2025)
This research aims to explore the transformation of Islamic da'wah in the digital era, with a specific focus on the transmission of Hadith through social media platforms such as Instagram, YouTube, and TikTok. Employing a qualitative content analysis method, the study investigates how Hadith is presented, contextualized, and disseminated across these platforms. Data were collected through purposive sampling of selected da'wah content and analyzed thematically to identify emerging patterns and trends. The findings reveal four key aspects: (1) the simplification and visual adaptation of Hadith to enhance accessibility and audience engagement; (2) the rise of new digital religious influencers who often lack formal scholarly credentials; (3) concerns regarding the authenticity and accurate attribution of Hadith sources; and (4) the use of creative digital aesthetics to attract and retain viewers. These results highlight both the opportunities and challenges posed by digital media in the context of Islamic preaching. On one hand, digital platforms significantly broaden the outreach of religious messages; on the other hand, they demand careful consideration of content integrity and interpretive authority. This study contributes to a deeper understanding of religious communication in the digital age and offers practical insights for promoting a balance between innovation and authenticity in online da'wah practices.